Human Resources Development in Increasing Sales Turnover of Synthetic Rattan Products - Mimin Yatminiwati; Riza Bahtiar Sulistyan; Zainul Hidayat; Fauzan Muttaqien (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study was made with the aim of analyzing Human Resource Development in Increasing Sales Turnover of Synthetic Rattan Products by Dfanda Synthetic Rattan. The research method used is descriptive analysis using a qualitative research approach. The data collection technique carried out by the researcher was to conduct interviews and direct observations to the business owner. In addition, there are additional supporting data from reading books and other sources related to the research title. The analyzed using SWOT analysis to find out what are the strengths, weaknesses, opportunities, and threats of human resource development carried out by the company. The results of human resource development research to increase employee productivity Dfanda Rattan synthetic is the business partner model strategy because this strategy has several advantages, namely the existence of several strengths within the company that can be used to take advantage of several opportunities and face several threats to the company as shown by the Cartesian diagram that the company is in quadrant I, namely aggressive with the implementation of the Growth Oriented Strategy which is a very profitable situation for the company. The company has the power so that it can take advantage of the opportunities that exist.